2018
DOI: 10.1016/j.carbpol.2018.01.103
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanogels condensed to ferulic acid for the essential oil of Lippia origanoides Kunth encapsulation

Abstract: In order to enable the applicability of the essential oil of Lippia origanoides Kunth, increasing its stability and dispersion in aqueous base, were prepared nanogels of chitosan modified with ferulic acid to be used in their encapsulation. The results obtained by FTIR and C SSNMR revealed the formation of CS-FA link in the different synthesized nanogels, while the studied by DLS showed particles with varied sizes and positive charge. A satisfactory encapsulation capacity of the essential oil was obtained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…In L. origanoides oil, p-cymene was the most abundant compound, followed by carvacrol and γterpinene. These results differ from those obtained in other studies (51,4), which found a higher proportion of carvacrol (41.1-49.7%), with p-cymene being the second most abundant compound. Isolated carvacrol from L. origanoides showed antifungal activity against A. fumigatus and A. flavus (10), and p-cymene from the same plant was effective against Trypanosoma cruzi and Leishmania chagasi (28).…”
Section: Chemical Composition Of the Essential Oils Of Lippia Sppcontrasting
confidence: 99%
“…In L. origanoides oil, p-cymene was the most abundant compound, followed by carvacrol and γterpinene. These results differ from those obtained in other studies (51,4), which found a higher proportion of carvacrol (41.1-49.7%), with p-cymene being the second most abundant compound. Isolated carvacrol from L. origanoides showed antifungal activity against A. fumigatus and A. flavus (10), and p-cymene from the same plant was effective against Trypanosoma cruzi and Leishmania chagasi (28).…”
Section: Chemical Composition Of the Essential Oils Of Lippia Sppcontrasting
confidence: 99%
“…This technology can embed compounds and protect these ingredients against deterioration, volatile losses, or premature interaction with other ingredients [14]. In special, different research groups have investigated the utilization of essential oils or antioxidant agents encapsulation using different materials, such as chitosan nanoparticles [31,32], jelly-alginates complex microparticles [33], casein micelles [34] and β-cyclodextrin [27].…”
Section: Introductionmentioning
confidence: 99%
“…Nanogels have recently attracted scientific and industry attention because, as hydrogels, their well-defined structures can shift their morphology and shape when subjected to external inputs such as temperature, pH, salt, or magnetic fields. The faster swelling/deswelling characteristic feature of nanogels allied with their excellent permeation abilities, high load capacity, controlled release of active compounds, and faculty to enhance the solubilization of numerous hydrophobic substances, are important advantages when applied as nanocarriers [ 27 , 66 , 67 , 68 ].…”
Section: Bionanocomposites Preparation For Food Processing Applicationsmentioning
confidence: 99%